A new approach for assessing the future of aquifers supporting irrigated agriculture. Issue 5 (12th March 2016) - Butler, James J.; Whittemore, Donald O.; Wilson, Blake B.; Bohling, Geoffrey C.
Abstract: Aquifers supporting irrigated agriculture are under stress worldwide as a result of large pumping‐induced water deficits. To aid in the formulation of more sustainable management plans for such systems, we have developed a water balance approach for assessing the impact of proposed management actions and the prospects for aquifer sustainability. Application to the High Plains aquifer (HPA) in the state of Kansas in the United States reveals that practically achievable reductions in annual pumping (<22%) would have stabilized areally averaged water levels over much of the Kansas HPA from 1996 to 2013. This demonstrates that modest pumping reductions can have a significant impact and highlights the importance of reliable pumping data for determining the net inflow (capture) component of the water balance. The HPA is similar to many aquifers supporting critically needed agricultural production, so the presented approach should prove of value far beyond the area of this initial application. Key Points: Water balance approach developed to assess prospects for sustainability of heavily stressed aquifers Net inflow (capture) term in water balance is directly estimated from water level and pumping data Modest pumping reductions can lead to stable water levels over much of High Plains aquifer in Kansas